2020
DOI: 10.1016/j.ijpharm.2020.119538
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of binary and ternary solvent systems for dermal delivery of methadone

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Additionally, several studies in the scientific literature have reported that combinations of solvents with differing physicochemical properties resulted in synergistic enhancement of drug permeation [ 58 , 59 , 60 , 61 , 62 , 63 ]. Brinkmann and Muller-Goymann (2003) investigated the effect of isopropanol (IPA) and a long-chain fatty acid ester, namely isopropyl myristate (IPM), on the permeation of hydrocortisone (HC) across isolated human SC [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several studies in the scientific literature have reported that combinations of solvents with differing physicochemical properties resulted in synergistic enhancement of drug permeation [ 58 , 59 , 60 , 61 , 62 , 63 ]. Brinkmann and Muller-Goymann (2003) investigated the effect of isopropanol (IPA) and a long-chain fatty acid ester, namely isopropyl myristate (IPM), on the permeation of hydrocortisone (HC) across isolated human SC [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, a combination of MCT and DEGEE at different ratios were prepared, each of their solubility capacities was evaluated using the same method. It has been reported before that the combination of binary solvents could promote skin permeation though a mechanism that is not well known yet [ 38 ]. Therefore, the combination of DEGEE and MCT was selected to be used for the formulation of the nanoemulsion.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of action for PG and fatty acids were systematically reviewed by Lane [ 35 ]. PG is a solvent that is widely used in topical formulations, and the uptake of PG in human skin has been reported previously [ 36 , 37 , 38 ]. The solubility of NIA in PG has been previously reported as 28% ( w/v ) at 32 °C [ 25 ].…”
Section: Resultsmentioning
confidence: 99%